Living Quran: Tabaruk Tradition in The Practice of The Book of Nurul Burhan at Nahdlatul Ulum Islamic Boarding School - Supe'i Supe'i; Sholahudiin Al Ayubi (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2022)
Abstract: This study discusses tabaruk at the salafiyah Islamic boarding school Nahdhtaul Ulum in Tangerang, with experience from the Nurul Burhan book. The issue is that many people seek tabaruk in three forms: objects, sacred people, and water. The field research method employs descriptive, qualitative methods with a phenomenological approach. Phenomenology is a description of the general meaning of a group of people's various life experiences related to concepts or phenomena. The study's findings are as follows: a tradition of practicing the book of Manaqib Nurul Burhan at the Nahdlatul Ulum Islamic Boarding School, Kresek, Tangerang, Banten Regency is carried out on the night of the 11th of every Hijriyah month on the basis of the caregiver's understanding solely for worship, getting students used to turning to shoibul manaqib, namely Sheikh Abdul Qadir Al-Jailani, and having every effort accompanied by fasting and prayer. Santri passionately believes in the truth of the virtues and blessings of Sheikh Abdul Qadir Al-Jailani, who is famous for his karomah and dubbed the leader of the guardians, thus making his own motivation for students to always practice this manaqib, so that teachers always provide motivation and increase the spirit of students and demand students in practicing the tabbarukan tradition. Keywords: Living Qur'an, Tradition, Tabaruk, Practice of the book of Nurul Burhan.